Reassessing private practice in public hospitals in Ireland An overview of OECD experiences - Mueller, Michael (OECD Health Working Papers, 2020)
In 2017, the "Sláintecare Report" proposed a comprehensive overhaul of the Irish health system including a reform proposal to phase out private practice in public hospitals to end the unequal treatment of public and private patients - private patients typically have quicker access to care - and reduce waiting times for public patients. This paper summarises the arguments for and against this practice that were put forward to help inform the subsequent policy debate. The paper compares how private practice is regulated and organised in Ireland with the situation in four other OECD countries - Australia, France, Israel and the United Kingdom - and discusses the costs and benefits of private practice in public hospitals, and highlights potential consequences of a ban on this practice. It also describes the information required when making a decision whether to ban this practice or not. Finally, the paper discusses some alternative policy approaches that could replace or complement a ban of private practice to discontinue the unequal treatment of public and private patients